2015
DOI: 10.1136/annrheumdis-2015-eular.4145
|View full text |Cite
|
Sign up to set email alerts
|

OP0017 Pregnancies in Patients with Rheumatoid Arthritis: Treatment Decisions, Course of the Disease, and Pregnancy Outcomes

Abstract: BackgroundObservational data so far suggest that biologic disease modifying antirheumatic drugs (bDMARDs) can be safely used in patients with rheumatoid arthritis (RA) until conception/awareness of pregnancy. However, little is known about the course of the disease during pregnancy in women who stopped bDMARDs in the first trimester, how to treat high disease activity (e.g. glucocorticoid use) and the influence of treatments on the birth outcome.ObjectivesTo study the outcomes of pregnancies and the courses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The rationale for doing so is that some side effects are mainly related to exposure later during pregnancy, e.g., prednisone has been associated with shorter gestational age (6), gestational hypertension, gestational diabetes, and premature rupture of the membranes (12), side effects that are most prominent during thirdtrimester exposure. Since lowering medication during pregnancy increases the risk of a flare of disease activity (13,14), it would be useful to identify those female RA patients in whom medication can be tapered safely in the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for doing so is that some side effects are mainly related to exposure later during pregnancy, e.g., prednisone has been associated with shorter gestational age (6), gestational hypertension, gestational diabetes, and premature rupture of the membranes (12), side effects that are most prominent during thirdtrimester exposure. Since lowering medication during pregnancy increases the risk of a flare of disease activity (13,14), it would be useful to identify those female RA patients in whom medication can be tapered safely in the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies were identified that assessed the impact of biologic drugs as a whole on pregnancy outcomes [255][256][257][258][259]. These studies included a total of 379 pregnancies in women with autoimmune disease on predominantly anti-TNFa drugs, but also rituximab (RTX), abatacept (ABA), tocilizumab (TCZ), ustekinumab (UST) and anakinra.…”
Section: Biologic Dmardsmentioning
confidence: 99%
“…TNFi exposure in pregnancy and with breastmilk exposure has been extensively studied since our last search. We identified an additional 50 studies, reporting 12 491 pregnancy exposures to TNFi, including INF (n 5377), ADA (n 2797), ETA (n 2210), CZP (n 776) and GOL (n 196) [37,[255][256][257][258][259]. Many studies reported combined outcomes for exposure to different TNFi agents.…”
Section: Anti-tnfa Drugsmentioning
confidence: 99%